Quantum magnetization exchange through transient hydrogen bond matrix defines magnetic resonance signal relaxation and anisotropy in central nervous system - Dmitriy A. Yablonskiy; Alexander L. Sukstanskii (Scientific Reports)
Abstract The integrity of cellular membranes (lipid bilayers) and myelin sheaths covering axons is a crucial feature controlling normal brain structural and functional networks. Yet, in vivo evaluation of this integrity at the nanoscale level of the cellular membranes organization is challenging. Herein we explore the dual property of biological water in Central Nervous System (CNS), as one of the major stabilizing factors of cellular membranes, and the major source of MRI signal. We introduce the Basic Transient Hydrogen Bond (THB) model of the MR signal relaxation due to the quantum spin/magnetization exchanges within the THB Matrix encompassing water molecules and membrane-forming macromolecules. Our data show the existence of two THB Matrix components with distinct lifetimes – one in a few nano-second range, and another in the range of tens nanoseconds. Importantly, the former component facilitates longitudinal relaxation of MR signal, the latter contributes to its transverse relaxation and causes the anisotropy of MR signal relaxation. These distinct features offer opportunity to study nanoscale level microstructure of cellular membranes. Furthermore, the ability to differentiate distinct THB Matrix components based on their MR signal relaxation properties can be fundamental to identifying pathological changes and enhancing disease visibility on MRI scans.